Polymorphisms in Brucella Carbonic Anhydrase II Mediate CO2 Dependence and Fitness in vivo - García Lobo, Juan M.; Ortiz, Yelina; Gonzalez-Riancho, Candela; Seoane, Asunción; Arellano-Reynoso, Beatriz; Sangari, Félix J. (Frontiers in Microbiology, 2019)
Some Brucella isolates are known to require an increased concentration of CO2 for growth, especially in the case of primary cultures obtained directly from infected animals. Moreover, the different Brucella species and biovars show a characteristic pattern of CO2 requirement, and this trait has been included among the routine typing tests used for species and biovar differentiation. By comparing the differences in gene content among different CO2-dependent and CO2-independent Brucella strains we have confirmed that carbonic anhydrase, CA II, is the enzyme responsible for this phenotype in all the Brucella strains tested. Brucella species contain two carbonic anhydrases of the β family, CA I and CA II; genetic polymorphisms exist for both of them in different isolates, but only those putatively affecting activity of CA II correlate with the CO2 requirement of the corresponding isolate. Analysis of these polymorphisms does not allow the determination of CA I functionality, while the polymorphisms in CA II consist of small deletions that cause a frameshift that changes the C-terminus of the protein, probably affecting its dimerization status, essential for the activity. CO2-independent mutants arise easily in vitro, although with a low frequency ranging from 10-6 to 10-10 depending of the strain. These mutants carry compensatory mutations that produce a full length CA II. At the same time, no change was observed in the sequence coding for CA I. A competitive index assay designed to evaluate the fitness of a CO2-dependent strain compared to its corresponding CO2-independent strain revealed that while there is no significant difference when the bacteria are grown in culture plates, growth in vivo in a mouse model of infection provides a significant advantage to the CO2-dependent strain. This could help explain why some Brucella isolates are CO2-dependent in primary isolation. The polymorphism described here also allows the in silico determination of the CO2 requirement status of any Brucella strain.